ANALISIS PANAI DAN MAHAR SEBAGAI INSTRUMEN STATUS EKONOMI MASYARAKAT DALAM PERKAWINAN ADAT BUGIS - Rizal Saputra; Muhammad Naufal Isandi; Aqmal Ferdian Putra (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study examines panai and mahar as instruments that reflect the economic status within Bugis society. Both elements play a central role in marriage customs and function as symbols of the groom’s financial capability. In practice, the increasing value of panai and mahar often creates a considerable economic burden for men, influencing social dynamics and marriage decisions. This research employs a quantitative approach using secondary data obtained from scholarly journals, books, and other relevant publications. The findings indicate that panai and mahar serve not only as cultural traditions but also as indicators of family social and economic standing. These results highlight that such practices can shape household economic patterns and affect men’s access to marriage within Bugis communities. This study examines panai and mahar as instruments that reflect the economic status within Bugis society. Both elements play a central role in marriage customs and function as symbols of the groom’s financial capability. In practice, the increasing value of panai and mahar often creates a considerable economic burden for men, influencing social dynamics and marriage decisions. This research employs a quantitative approach using secondary data obtained from scholarly journals, books, and other relevant publications. The findings indicate that panai and mahar serve not only as cultural traditions but also as indicators of family social and economic standing. These results highlight that such practices can shape household economic patterns and affect men’s access to marriage within Bugis communities.